Augmented Reality in Interactive Marketing : The State-Of-The-Art and Emerging Trends - Riar, Marc; Korbel, Jakob J.; Xi, Nannan; Meywirth, Sophia; Zarnekow, Rüdiger; Hamari, Juho (Palgrave Macmillan, 2023)
Recent years have seen a swift embracement of augmented reality (AR) as an interactive marketing tool, which has been accelerated even more rapidly by the COVID-19 pandemic. However, the general attitude toward the technology as well as the factors that inhibit or facilitate its adoption from both, the consumers, and practitioners, remain elusive. This prevents marketers from fully exploiting the potential related to AR marketing. This chapter (1) draws on current literature to conceptualize consumer experience in AR marketing and (2) complements these findings with a practitioner perspective by conducting interviews with small retailers. The results of the present chapter indicate that, from the consumer perspective, AR can give rise to diverse cognitive, affective, and social-psychological outcomes, which can translate into behavioral outcomes, including purchase intentions, word-of-mouth intentions, and brand engagement. From the practitioner’s perspective, initial interview results reveal that advancements toward an easy integration of AR within existing IT infrastructures, as well as efficient ways to create virtual product replicas are crucial for the adoption of AR by small retailers. Based on the combined observations from literature and the conducted interviews, a comprehensive framework of interactive AR marketing is provided, and a way forward is discussed by addressing the emergent trends of AR as an interactive marketing technology.
Keywords: Interactive marketing; Shopping; Retail; Consumer experience; augmented reality; fi=Tietojärjestelmätiede|en=Information Systems|